2013
DOI: 10.1103/physrevc.87.054902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial-state fluctuations on jet-energy loss

Abstract: The effect of initial state fluctuations on jet energy loss in relativistic heavy-ion collisions is studied in a 2+1 dimensional ideal hydrodynamic model. Within the next-to-leading order perturbative QCD description of hard scatterings, we find that a jet loses slightly more energy in the expanding quark-gluon plasma if the latter is described by the hydrodynamic evolution with fluctuating initial conditions compared to the case with smooth initial conditions. A detailed analysis indicates that this is mainly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…As an outlook, we plan to study the effect of event-by-event fluctuations as presently done e.g. in [91][92][93]. almost energy independent at the LHC.…”
Section: Discussionmentioning
confidence: 99%
“…As an outlook, we plan to study the effect of event-by-event fluctuations as presently done e.g. in [91][92][93]. almost energy independent at the LHC.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [51] it was found that with the inclusion of the transverse expansion of the medium, i.e., using a (2+1)-dimensional hydrodynamic model, jet energy loss is enhanced when the initial state fluctuation is incorporated. A detailed investigation has also been implemented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the initial state fluctuations on heavy quarks has not yet been studied. There have been similar studies of the effect of the initial state fluctuations in the context of high p T light flavor jets [49,50,51], but no unified conclusion has been reached yet. For instance, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we discuss the influence of fluctuating versus smooth initial conditions. This latter aspect was studied in the frame-work of (light-hadron) jet physics [15][16][17], but only recently attracted attention in the context of heavy-quark observables [18], where contrary to the present work it is found that the energy loss of heavy quarks is enhanced in a medium with local fluctuations. …”
Section: Introductionmentioning
confidence: 93%